(untitled) (Innovaciones Educativas, 2024)
The Chilean history curriculum and textbooks on the subject feature an adult-centered narrative that excludes children’s participation in the study of the past, focusing on describing the political, economic, and military exploits of adult men representing the ruling sectors. To address this problem, this paper offers a philosophical-educational reflection on the importance of redefining the historical role of children in order to deconstruct children as banished actors of school history or as subaltern subjects of the adult world. From a methodological point of view, this paper is based on the documentary review of different texts housed in databases such as Scielo, Clacso, Redalyc, Wos, Scopus, ProQuest, Latindex and Dialnet. The texts selected are mainly from Chile, Mexico and Spain and examine the importance of rethinking the current treatment of children in the Chilean history curriculum, especially in history textbooks. The search was conducted using the following keywords: Chile, school history, childhood, national curriculum, textbooks, adultcentrism, history didactics and historical thinking. The argumentative method was used to provide theoretical support for the reflection. In conclusion, it is fundamental to adopt a child’s perspective in history in order to help children become critical citizens, aware of their rights and responsibilities.